External Dimension of Constitutionalisation of the Rule of Law and Human Rights - Marcheva, Deyana (Yearbook of the Law Department, 2023)
The rule of law and the protection of human rights have emerged as the cornerstone of the European Union’s law and policies particularly in the context of East-ward enlargement. This process has not only served as a "laboratory" for the transformation of candidate countries but has also triggered changes significant in the European Union itself, contributing to its "constitutional awakening". Bulgaria’s accession to the Council of Europe and the EU brought about a profound structural shift in its constitutional paradigm, fundamentally altering the understanding and implementation of the rule of law and human rights protection. In this context, it is essential to reevaluate the traditional template of Westphalian constitutionalism in Bulgaria and to recognize the external dimension of principles’ constitutionalization as an "anchor" that will keep Bulgaria’s democracy, rule of law, and human rights stable despite internal and external turmoil.